'Far more deeply interfused': 'Tintern Abbey' between Burkean and Kantian Sublimity. Issue 1 (April 2022) - Sommer, Tim
Abstract : This essay traces the presence of eighteenth-century aesthetics in Wordsworth's 'Tintern Abbey'. It argues that the poem's use of the term 'sublime' is more than just accidental. Rather than merely rehearsing a contemporary aesthetic commonplace, Wordsworth's references to the sublime are intertextually linked to two eighteenth-century models of the concept, the one outlined in Edmund Burke's A Philosophical Enquiry into the Origin of Our Ideas of the Sublime and Beautiful (1757), the other developed in Immanuel Kant's Critique of Judgement (1790). Proceeding from a delineation of the Burkean and Kantian semantics of sublimity and a reading of their reverberations in Wordsworth's prose fragment 'The Sublime and the Beautiful', the essay suggests that 'Tintern Abbey' juxtaposes a sensationist sublime modelled on Burke's Enquiry with the intellectualist understanding of the term formulated in Kant's third Critique .